THE INFLUENCE OF ECONOMIC INCOME AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE - Harin Tiawon; Ferdinand; Vivy Kristinae; Meitiana (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2024)
Objective – This research aims to determine the influence of economic income and organizational culture on the performance of Central Kalimantan Province Revenue Service employees. It is important to improve performance that has a positive impact on the independent variable, so quantitative testing is carried out.Design/Methodology/Approach – This research method is descriptive and quantitative with the SPSS 23.0 analysis tool. The results of the research are to provide information on the research problem, and at the same time connect the formulation, benefits in the research hypothesis as cause and effect which are used to answer statements from the questionnaire. The type of sample data is primary data with a questionnaire of 100 people, Revenue Service employees.Findings – The results of research on economic income, organizational culture, and employee performance have a significant positive effect of 71% on employee performance. This means that the higher the independent role of organizational culture and economic income, the better employee performance will be.Conclusion and Implications – The results provide implications, to pay more attention to the role of organizational culture and performance according to economic income so that the main tasks and job functions are not disturbed in improving employee performance. For further research, we can examine transformational leadership style variables